Tuberculosis: knowledge among nursing undergraduate students - Carvalho,Cleina de Fátima (2019)
ABSTRACT Objective: To analyze the knowledge about tuberculosis among nursing undergraduate students of a Federal Higher Education Institution. Method: Descriptive cross-sectional study, with quantitative approach. Data were collected through a questionnaire based on the WHO’s guide to developing evaluation instruments on knowledge, attitudes and practices related to TB. Students were classified as “with knowledge” and “with little knowledge” based on the mean percentage of correct responses to the variables analyzed. Descriptive statistics techniques were used. Results: 60 nursing students were interviewed. “with little knowledge” was observed among students who were studying at the university for less time and who had no previous contact with the subject, and “with knowledge” was observed among those whose knowledge about tuberculosis was acquired in the health services. Conclusion: Knowledge gaps among undergraduate nursing students were identified, suggesting the need to rethink teaching-learning strategies on the subject.